2013
DOI: 10.1111/ajd.12028
|View full text |Cite
|
Sign up to set email alerts
|

Nasal carriage of Staphylococcus aureus in patients undergoing Mohs micrographic surgery is an important risk factor for postoperative surgical site infection: A prospective randomised study

Abstract: Nasal S. aureus carriage is an important risk factor for SSI in MMS, conferring an over threefold increase in SSI risk. A pre-operative nasal swab provides a simple and effective risk stratification tool. The use of a topical decolonisation regimen reduces the infection rate in carriers to a level approaching non-carriers without exposure to systemic antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 16 publications
1
38
0
3
Order By: Relevance
“…The quinoline-derived cationic antimicrobial HT61 [1] was initially developed to improve the success of nasal decolonisation interventions aimed at decreasing the risk of post-operative surgical site infections (SSI) posed by carriage of methicillin resistant Staphylococcus aureus (MRSA) [2,3] . However, more recently it has been proposed as a resistance breaker to be used in conjunction with other more established antimicrobials [4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quinoline-derived cationic antimicrobial HT61 [1] was initially developed to improve the success of nasal decolonisation interventions aimed at decreasing the risk of post-operative surgical site infections (SSI) posed by carriage of methicillin resistant Staphylococcus aureus (MRSA) [2,3] . However, more recently it has been proposed as a resistance breaker to be used in conjunction with other more established antimicrobials [4] .…”
Section: Introductionmentioning
confidence: 99%
“…In bilayers containing 25 mol% phosphatidylglycerol, neutron reflectometry data suggests that exposure to HT61 increases the level of solvent in the hydrophobic region of the membrane, which is indicative of gross structural damage. Increasing the proportion of PG elicits a concomitant level of membrane damage resulting in almost total destruction when 75 mol% phosphatidylglycerol is present.We therefore propose that HT61's primary action is directed towards the cytoplasmic membrane of Gram positive bacteria.The quinoline-derived cationic antimicrobial HT61 [1] was initially developed to improve the success of nasal decolonisation interventions aimed at decreasing the risk of post-operative surgical site infections (SSI) posed by carriage of methicillin resistant Staphylococcus aureus (MRSA) [2,3] . However, more recently it has been proposed as a resistance breaker to be used in conjunction with other more established antimicrobials [4] .…”
mentioning
confidence: 99%
“…23,[27][28][29] However, recent reviews have been unable to show definitive evidence that preoperative showering reduces SSI. [33][34][35][36][37] Investigations from various surgical disciplines have shown a reduction in SSI to a rate comparable with noncarriers with the use of protocols to identify and decolonize carriers of S. aureus before surgery. It has been shown that nasal carriage of S. aureus is an independent risk factor for the development of SSI in multiple surgical settings, including dermatologic surgery.…”
Section: Preoperative Decolonizationmentioning
confidence: 99%
“…It has been shown that nasal carriage of S. aureus is an independent risk factor for the development of SSI in multiple surgical settings, including dermatologic surgery. 37 A variety of decolonization protocols have been described, usually consisting of topical agents used [38][39][40][41] It remains to be seen if these interventions are beneficial in a dermatologic surgery setting, but a recent prospective randomized study demonstrated a significant reduction in SSI after Mohs surgery among nasal S. aureus carriers with the use of a topical decolonization regimen.…”
Section: Preoperative Decolonizationmentioning
confidence: 99%
“…The most well-established regimen recommended in several national guidelines (e.g., in the 1998 United Kingdom guideline and the upcoming U.S. CDC guideline) is using a combination of 5 to 7 days of treatment with nasal mupirocin ointment and chlorhexidine soap (4,5,(10)(11)(12). This treatment has been shown to reduce the incidence of nosocomial infections (5).…”
mentioning
confidence: 99%